Assessment of groundwater quality using GIS in Kurud block of Dhamtari district Chhattisgarh - KUMAR, AEKESH; TRIPATHI, M. P.; KHALKHO, DHIRAJ; BAGHEL, SHREEYA (Journal of Soil and Water Conservation, 2021)
This paper examines the quality of groundwater of Kurud block, Durg district of Chhattisgarh state, which comes under the semi-critical block with 78% groundwater development. During this study, ten groundwater samples which represent the entire block were collected during the post-monsoon period to determine its suitability for drinking and irrigation purpose. Sixteen groundwater quality parameters namely pH, EC, TDS, chloride, fluoride, calcium, magnesium, sodium, potassium, sulfate, total hardness, carbonate, bicarbonate, nitrate, manganese, and arsenic were analyzed at CGWB, NCCR Raipur. Based on the above parameter for irrigation purpose percentage sodium, Sodium absorption ratio (SAR), Residual sodium carbonate (RSC), Soluble sodium percentage (SSP) and Permeability Index (PI) were calculated. Water Quality Index (WQI) has been a useful tool for water quality monitoring programs, to evaluate the impacts of corrective measures on water quality and also useful for the suitability of groundwater for drinking purposes was also estimated. The present study block shows that 10% of samples were falling under the excellent category, 70% samples were falling under the good category and rest 20% samples were falling under the poor category as per the WQI classification. The index map provides a comprehensive picture which is easily interpretable for the decision-makers for better planning and management of water resources for drinking and irrigation purpose.